Ill wind - Barr, Nevada (Barr, Nevada. Anna Pigeon novel., 2004)
"Lately, visitors to Mesa Verde have been bringing home more than photos--they're also carrying a strange, deadly disease. And once it strikes, park ranger Anna Pigeon must find the very human source of the evil wind."--Amazon.com.